"Ex-Muslims, " Bible Prophecy, and Islamophobia: Rhetoric and Reality in the Narratives of Walid Shoebat, Kamal Saleem, Ergun and Emir Caner. Issue 2 (1st October 2014) - ,
Abstract : The connection between Christian dispensationalism ("rapture" theology) and anti-Muslim sentiments is an understudied topic often missing from the scholarship on Islamophobia. This paper is an attempt to fill this gap by focusing on the problematic narratives of four prominent "ex-Muslim" converts to Christianity: Walid Shoebat, Kamal Saleem, Ergun and Emir Caner. I argue that these men have used their Middle Eastern heritages to coax the public into believing that they are former terrorists in order to sell books, demonize Islam, and promote their particular interpretation of Christianity.